Perbandingan Maserasi Daun Pala, Daging Pala dan Biji Pala sebagai Agen Antibakteri Terhadap bakteri Staphylococcus aureus - Meka Faizal Farabi; yusuf eko Nugroho (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Staphylococcus aureus is a pathogenic bacterium that can cause various infections in humans and has the potential to develop antibiotic resistance. The utilization of medicinal plants as natural antibacterial agents has gained increasing attention, including nutmeg (Myristica fragrans Houtt.), which is known to contain various bioactive compounds. This study aimed to compare the antibacterial activity of nutmeg leaf, seed, and mace infusions against Staphylococcus aureus. The study was conducted using an experimental laboratory design with the agar well diffusion method. Infusions were prepared using a 1:10 (w/v) ratio of simplicia to distilled water and heated at 90°C for 15 minutes. A suspension of S. aureus was inoculated onto Mueller Hinton Agar (MHA), followed by antibacterial activity testing using leaf, seed, and mace infusions. The inhibition zone diameters were measured after incubation at 37°C for 24 hours. The results showed that nutmeg leaf infusion produced an average inhibition zone diameter of 13.67 ± 1.53 mm, whereas seed and mace infusions did not produce any inhibition zones. These findings indicate that only nutmeg leaf infusion exhibited antibacterial activity against S. aureus under the conditions of this study. Therefore, nutmeg leaves have the potential to be developed as a natural antibacterial agent that can be easily applied through a simple infusion method. Further studies are recommended to evaluate the phytochemical profile, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) to support its development as an antibacterial agent.